EVALUASI PEMANFAATAN MEDIA SOSIAL BAGI PELAKSANAAN FUNGSI ANGGOTA DPRD JAWA TENGAH - Wahid Abdulrahman, dkk (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
In order to improve the performance of Central Java Parliament, social media has been used as a tool that is easy, inexpensive, and could reach all segments throughout the region of Central Java. This study aimed to evaluate the use of social media in the implementation of the functions of legislators to communicate with the public. This research is a qualitative research with case study method. Capturing data through in-depth interviews to Central Java Parliament members who are active in social media and the public in their networks. The results of the study consisted of three things. First, social media is used by members of the Central Java Parliament for three reasons: (1) communicate the functions of the parliament (legislative, control, and budget); (2) communicate with the public in order to listen public needs and get feedback; (3) a means of self entertainment by using social media as a tool to express their selves and share personal information. Second, related to the function of the parliament which has been communicated through social media, the control function is the most frequent performed. While the legislative function performed moderately, and the budget function as the most rarely communicated. Third, public informants in social media networks of Central Java parliament members perceives the them as representatives of the people who actually work for the people. Keywords: social media, members of the board, the function of parliamen.